Synthesis, Characterization, and Evaluation of Antimicrobial and Antifertility Efficacy of Heterobimetallic Complexes of Copper (II) - Ashu Chaudhary; Anshul Singh (Journal of Chemistry)
Heterobimetallic complexes of the copper with remarkable antimicrobial and antifertility action have been synthesized by the conventional method by reacting CuCl2 and o-phenylenediamine in the methanolic medium forming the mononuclear complex of the type CuC6H8N22Cl2 which was further treated with group 4 or 14 organometallic dichlorides (Ph2M′Cl2, Me2M′Cl2, and Cp2M′′Cl2) [M′ = Sn, Si, and M′′ = Ti, Zr] leading to formation of heterobimetallic complexes. All the synthesized complexes were characterized in the light of various physicochemical techniques like elemental analyses, conductivity measurements, molecular weight determination, electronic and infrared spectra, electronic spin resonance, X-ray, and mass spectral studies. The in vitro antibacterial activity of synthesized complexes against Escherichia coli and Staphylococcus aureus was tested to evaluate their inhibiting activities. The antifungal activities of mono- and heterobimetallic complexes were studied by screening the compounds against Fusarium oxysporum and Alternaria alternata. These complexes were then investigated to reveal their effect on the reproductive organs of male rats. The treatment has shown substantial decline in the sperm motility and density signifying the imperious antifertility activity.